Revisit to diffraction anomalous fine structure. (1st October 2014) - Kawaguchi, T.; Fukuda, K.; Tokuda, K.; Shimada, K.; Ichitsubo, T.; Oishi, M.; Mizuki, J.; Matsubara, E.
<x xml:space="preserve">Abstract</x> The diffraction anomalous fine structure (DAFS) method that is a spectroscopic analysis combined with resonant X‐ray diffraction enables the determination of the valence state and local structure of a selected element at a specific crystalline site and/or phase. This method has been improved by using a polycrystalline sample, channel‐cut monochromator optics with an undulator synchrotron radiation source, an area detector and direct determination of resonant terms with a logarithmic dispersion relation. This study makes the DAFS method more convenient and saves a large amount of measurement time in comparison with the conventional DAFS method with a single crystal. The improved DAFS method has been applied to some model samples, Ni foil and Fe3O4 powder, to demonstrate the validity of the measurement and the analysis of the present DAFS method.